Perceptions of Investment Risk Associated with Material Control Weakness Pervasiveness and Disclosure Detail - Rose, Jacob M.; Norman, Carolyn Strand; Rose, Anna M. (The Accounting Review, 2010)
ABSTRACT: This research examines whether investors adjust their assessments of investment risk in response to material control weakness disclosures, the pervasiveness of material control weaknesses, and the detail of explanation provided regarding the pervasiveness of material control weaknesses. Findings from a laboratory experiment with 97 nonprofessional investors, a second experiment with 53 nonprofessional investors, and surveys of 47 investors and 28 Fortune 500 directors confirm prior archival findings that investors adjust their investment risk assessments in response to material weakness disclosures. More importantly, we find evidence of an interactive effect of material control weakness pervasiveness and disclosure detail that is counter to the expected benefits of expanded disclosure desired by corporate directors. When material weakness disclosures include specific and detailed discussion of the pervasiveness of control weaknesses, investors increase assessments of investment risk for less pervasive weaknesses and decrease assessments of risk for more pervasive weaknesses. Results indicate that these findings are driven by different levels of investor trust in management.